2022
DOI: 10.3389/fpsyg.2022.825509
|View full text |Cite
|
Sign up to set email alerts
|

Different Dimensions of Grit as the Predictor of Job-Search Intensity and Clarity

Abstract: Job-search is considered as a developmental task for college students to move from campus to workplace. Based on the self-determination theory, 859 Chinese college students were selected as the study sample and hierarchical regression analysis was used to explore the perseverance of effort and consistency of interest on job-search intensity and clarity. The survey showed that the perseverance of effort has a significant positive effect on the job-search intensity, while it has no significant positive effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A study focusing on the students on academic probation in a university reported that consistency of interest was significantly associated with academic improvement whereas perseverance of effort showed no significant association with it [ 57 ]. In addition, another study suggested that the students with high consistency of interest were capable of maintaining their initial enthusiasm for their goals even in the face of difficulties [ 51 ]. Thus, for students with particularly low academic performance, consistency of interest may contribute both to maintaining their initial motivation for becoming medical doctors and to diminishing risk factors for depression, including stressful academic difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…A study focusing on the students on academic probation in a university reported that consistency of interest was significantly associated with academic improvement whereas perseverance of effort showed no significant association with it [ 57 ]. In addition, another study suggested that the students with high consistency of interest were capable of maintaining their initial enthusiasm for their goals even in the face of difficulties [ 51 ]. Thus, for students with particularly low academic performance, consistency of interest may contribute both to maintaining their initial motivation for becoming medical doctors and to diminishing risk factors for depression, including stressful academic difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting that there should be times when these dimensions should predict better together (e.g., West Point Graduation; Duckworth et al, 2007) and times when each dimension is a better predictor than the focal construct. For example, a recent study related to job search clarity found the perseverance dimension to be nonsignificant but passion to be significant (Yu et al, 2022). Building on these findings, we examine how political ideology can influence each facet of grit.…”
Section: Dimensions Of Gritmentioning
confidence: 99%
“…They continue to remain a key concept across different management theories concerning job performance (e.g., Campbell, 1990), work motivation (e.g., Jordan et al, 2019; Locke & Latham, 1990), entrepreneurship (e.g., Uy et al, 2015), organizational citizenship behavior (OCB) (e.g., Borman & Motowidlo, 1993; Lee et al, 2018), or strategic management (e.g., Waldman & Yammarino, 1999). Also, research, especially in academic settings, has shown that “staying on task” and “keeping on despite obstacles and fears” result in higher academic achievement (Wolters & Hussain, 2015), better grades (Muenks et al, 2017), higher productivity (Hodge et al, 2018), higher job‐search intensity after graduation (Credé et al, 2017; Yu et al, 2022), and higher “re‐employment efficacy” (Wanberg et al, 2010). Furthermore, due to the fact that persistent‐related constructs are perceived by management as more controllable than cognitive skills (Weiner et al, 1972), they are important factors in both employee evaluation and staffing decisions (Soliman & Buehler, 2018), usually with management promoting determined employees who have made a commitment to continue to try to improve.…”
Section: Introductionmentioning
confidence: 99%